2014
DOI: 10.1039/c3dt53291g
|View full text |Cite
|
Sign up to set email alerts
|

Hexahapto-lanthanide interconnects between the conjugated surfaces of single-walled carbon nanotubes

Abstract: We report the response of the electrical conductivity of semiconducting single-walled carbon nanotube (SWNT) thin films on exposure to metal vapors of the early lanthanides under high vacuum conditions. We attribute the strongly enhanced conductivities observed on deposition of samarium and europium to charge transfer from the metals to the SWNT backbone, thereby leading to the first examples of mixed covalent-ionic bis-hexahapto bonds [(η(6)-SWNT)M(η(6)-SWNT), where M = Sm, Eu].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…6 Deposition of lithium completely suppressed the S 11 transition, in accordance with its strongly electron donating nature. Similarly, the optical measurements showed that Sm and Eu almost completely suppress the S 11 peak, whereas in the case of ytterbium, there is still a detectable S 11 peak, suggesting a slightly weaker doping effect.…”
Section: ■ Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…6 Deposition of lithium completely suppressed the S 11 transition, in accordance with its strongly electron donating nature. Similarly, the optical measurements showed that Sm and Eu almost completely suppress the S 11 peak, whereas in the case of ytterbium, there is still a detectable S 11 peak, suggesting a slightly weaker doping effect.…”
Section: ■ Introductionmentioning
confidence: 65%
“…According to this model the stability of the bis-hexahaptolanthanide complexes depends on the accessibility of the 5d 1 6s 2 electronic structure and we have previously shown that such an analysis accounts for the variations in the conductivity enhancements measured for the series, Ln = La, Nd, Sm, Eu, Gd. 6 In this analysis, we suggested that the additional enhancement in the conductivities induced by Eu and Sm relative to the other lanthanides (La, Nd, Gd) was due to the ability of Eu and Sm to transfer electron density to the SWNT conduction band via the bis-hexahapto-bonds at the SWNT junctions. 6 Thus, it was of interest to explore the relationship of the Raman 2D peak shift because of electron density donation to the SWNTs (Figure 4a) with the promotion energy necessary to achieve the 4f m 5d 1 6s 2 lanthanide electronic configuration and it may be seen in Figure 4a that the Raman data suggest that Eu, Sm and Yb are able to transfer electrons to the SWNT conduction band.…”
Section: ■ Discussionmentioning
confidence: 95%
“…Herein, we wish to report on the structure of [Dy(dsp) 2 ] À . In the interim time, Magadur and co-workers first combined three-decker complexes [Ln 2 (dsp) 3 (EtOH)] with single walled carbon nanotubes (SWNT) [27][28][29][30][31] to produce Carbon Nanotube Field Effect Transistors (CNFET) [27, [32][33][34][35]. This work demonstrated that [Ln 2 (dsp) 3 (EtOH)] possesses the potential for applications to molecular electronic devices.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, the development of the organometallic chemistry of graphitic materials offers the potential to generate doped structures by use of transition metals which deviate from the traditional 18-electron rule [108,109], while providing electrical interconnects that are applicable to the bridging of any surface containing the benzenoid ring system, including single-walled CNTs, graphene and other graphitic carbons. In fact the organometallic approach outlined earlier may lead to new materials and phenomena and there are potential applications in a number of fields, such as atomic spintronics and organometallic catalysis.…”
Section: Discussionmentioning
confidence: 99%